2023
DOI: 10.1093/nar/gkad797
|View full text |Cite
|
Sign up to set email alerts
|

Where the minor things are: a pan-eukaryotic survey suggests neutral processes may explain much of minor intron evolution

Graham E Larue,
Scott W Roy

Abstract: Spliceosomal introns are gene segments removed from RNA transcripts by ribonucleoprotein machineries called spliceosomes. In some eukaryotes a second ‘minor’ spliceosome is responsible for processing a tiny minority of introns. Despite its seemingly modest role, minor splicing has persisted for roughly 1.5 billion years of eukaryotic evolution. Identifying minor introns in over 3000 eukaryotic genomes, we report diverse evolutionary histories including surprisingly high numbers in some fungi and green algae, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…On average, brown algal genes tend to be more intron-rich than those of the other stramenopile groups 15 , including closely-related sister species (Figure 2B), with the notable exception of Chrysoparadoxa australica , whose genes contain many short, C/T-rich introns (Figure 2B). The vast majority of splice sites in Phaeophyceae are of the canonical GT-AG type and no signatures of minor U12 introns were identified in intronic sequences, in accordance with a previous study 16 . Consistent with this observation, an analysis of spliceosome proteins using a recent reference dataset 17 found that, with the exception of ZCRB1, none of the 12 minor spliceosome genes were present in brown algal genomes (Table S3), indicating that the minor intron spliceosomal associated machinery was lost in the Phaeophyceae.…”
Section: Resultssupporting
confidence: 92%
“…On average, brown algal genes tend to be more intron-rich than those of the other stramenopile groups 15 , including closely-related sister species (Figure 2B), with the notable exception of Chrysoparadoxa australica , whose genes contain many short, C/T-rich introns (Figure 2B). The vast majority of splice sites in Phaeophyceae are of the canonical GT-AG type and no signatures of minor U12 introns were identified in intronic sequences, in accordance with a previous study 16 . Consistent with this observation, an analysis of spliceosome proteins using a recent reference dataset 17 found that, with the exception of ZCRB1, none of the 12 minor spliceosome genes were present in brown algal genomes (Table S3), indicating that the minor intron spliceosomal associated machinery was lost in the Phaeophyceae.…”
Section: Resultssupporting
confidence: 92%
“…These interactions provide a structural basis for the conservation of the minor intron 5′SS. The 5′ nucleotide of the U12-type 5′SS may be either A1 or G1 ( 30 , 31 ). In our structure, the 6′ NH 2 of A1 makes a putative H-bond to the carbonyl oxygen of Gly 17 from U11-35K.…”
Section: Recognition Of the U12-type 5′ssmentioning
confidence: 99%
“…RNU4ATAC is a non-coding gene transcribed into the small nuclear RNA (snRNA) U4atac, a component of the minor spliceosome. This ribonucleic complex excises less than one percent of all human introns, 12 and deficiency in its function leads in most cases to minor intron retention that impairs the correct maturation of about 750 minor-intron containing transcripts. 2,[13][14][15][16][17] Here, we report a particular case of a patient with TALS traits but no variant in RNU4ATAC.…”
Section: Introductionmentioning
confidence: 99%